Factors Influencing Self-Regulated Learning In Higher Education - Balapumi, Rohini; Aitken, Ashley (IADIS Press, 2012)
The concepts of independent learning (IL), self-directed learning (SDL) and self-regulated learning (SRL) have been widely used to understand students’ learning success. Often, these terms are linked with one another and used interchangeably in the literature with regards to students’ learning process. The purpose of this conceptual and review paper is (1) to promote conceptual clarity of these concepts by having clear definitions of the concepts of IL, SDL and SRL in the context of education and (2) to provide a review of research related to the development of students’ SRL strategies and skills in higher education. Based on findings from the literature, we deduce that engaging in the process of SRL can lead to achieving independent learning. We also presented a continuum of independent learning, describing the two extreme ends of learning: externally motivated, other-directed and other-regulated dependent learning and selfmotivated, self-directed and self-regulated independent learning. The literature review on SRL reveals that students’ academic self-regulation is influenced by their personal processes such as cognitive/metacognitive knowledge and motivational beliefs and also external entities such as lecturers and teaching materials in higher education.